Excessive Sodium and Insufficient Potassium Consumption Can Elevate the Risk of Developing Hypertension - Nanda Maharani Saqadifa; Ardesy Melizah Kurniati; Sadakata Sinulingga; Syarif Husin; Rizma Adlia Syakurah; Syarinta Adenina (Biomedical Journal of Indonesia, 2023)
Introduction. Physiologically, there are setbacks and weaknesses in body functions in the elderly. This can cause inadequate food intake or eating imbalances in the elderly. Increased blood pressure is influenced by many factors such as sodium and potassium intake and less potassium intake can increase blood pressure. The purpose of this study was to determine the relationship of sodium and potassium intake from food with blood pressure in the elderly in the community dr. Mohammad Hoesin Hospital. Methods. An observational-analytic study was conducted on 120 elderly people using a cross-sectional research design conducted in the elderly community of dr. Mohammad Hoesin Hospital in October-November 2019. The sample of this study were members of the elderly community aged over 60 years, present when the study was conducted, willing to become a respondent and signed an informed consent. Data was obtained through filling out food record questionnaires, food recall interviews, personal data interviews, and direct measurement of blood pressure and nutritional status. To meet the research objectives, data were analyzed by Chi-square test. Results. In this study, there were 120 elderly people consisting of 3 men and 117 women. There was a significant relationship between sodium and potassium intake and blood pressure (p=0,003 and p=0,0001). Conclusion. There is a significant relationship between sodium and potassium intake with blood pressure in the elderly.